A Novel Microfluidic-Based OMC-PEDOT-PSS Composite Electrochemical Sensor for Continuous Dopamine Monitoring - Sofwan Nuh; Apon Numnuam; Panote Thavarungkul; Tonghathai Phairatana (Biosensors, 2022)
Fast and precise analysis techniques using small sample volumes are required for next-generation clinical monitoring at the patient’s bedside, so as to provide the clinician with relevant chemical data in real-time. The integration of an electrochemical sensor into a microfluidic chip allows for the achievement of real-time chemical monitoring due to the low consumption of analytes, short analysis time, low cost, and compact size. In this work, dopamine, used as a model, is an important neurotransmitter responsible for controlling various vital life functions. The aim is to develop a novel serpentine microfluidic-based electrochemical sensor, using a screen-printed electrode for continuous dopamine detection. The developed sensor employed the composite of ordered mesoporous carbon (OMC) and poly (3,4 ethylenedioxythiophene)-poly (styrene sulfonate) (PEDOT-PSS). The performance of a microfluidic, integrated with the sensor, was amperometrically evaluated using a computer-controlled microfluidic platform. The microfluidic-based dopamine sensor exhibited a sensitivity of 20.2 ± 0.6 μA μmol L−1, and a detection limit (LOD) of 21.6 ± 0.002 nmol L−1, with high selectivity. This microfluidic-based electrochemical sensor was successfully employed to determine dopamine continuously, which could overcome the problem of sensor fouling with more than 90% stability for over 24 h. This novel microfluidic sensor platform provides a powerful tool for the development of a continuous dopamine detection system for human clinical application.